On Approach to Increase Integration Rate of Field-Effect Transistors by Using Inhomogeneity of Heterostructure and Optimization of Technological Process - L. Pankratov, Evgeny; A. Bulaeva, Elena (Micro and Nanosystems, 2014)
In this paper, we model mass and heat transport during manufacturing a field-effect transistor by diffusion or ion implantation in a heterostructure. Based on this modeling we formulate recommendations to optimize annealing of dopant and/or radiation defects to obtain distributions of concentrations of dopants with higher sharpness. The increasing sharpness gives us the possibility to increase integration degree of the field-effect heterotransistor. We also introduce an analytical approach to model redistribution of concentration of dopant and radiation defects and relaxation of spatio-temporal distribution of temperature.
Keywords: increase integration rate of transistors